Karyotype Ikan Mas (Cyprinus carpio Linnaeus 1758) Majalaya - Tuty Arisuryanti; Anjar Tri Wibowo (Journal of Tropical Biodiversity and Biotechnology, 2016)
Common carp (Cyprinus carpio Linnaeus 1758) is grouped into Family Cyprinidae and Order Cypriniformes. One of Indonesian common carp which is commonly domesticated in Indonesia to fulfil consumer needs of animal protein is “Majalaya”. Even though the common carp “Majalaya” is extensively domesticated to meet market demands, any comprehensive study on the fish chromosomes has not been investigated. Chromosome study on the common carp “Majalaya” is quite important related to breeding program including certification process. The objective of this study was to study karyotype of the common carp “Majalaya” collected from UKBAT Cangkringan, Yogyakarta. Chromosome preparation of the common carp “Majalaya” investigated in this study was a splash method with blood cell cultures. The results revealed that the common carp “Majalaya” has diploid chromosome number (2n) = 98 classified as 12 (6 pairs) metacentric chromosomes and 86 (43 pairs) telocentric chromosomes displaying karyotype formula 2n = 2x = 98 = 12 m + 86 t. However, sex chromosomes of the common carp “Majalaya” could not be identified in this study. In addition, the variation of total length chromosomes of the fish is between 1,052 μm and 3,299 μm. On the basis of R value (3,079 ± 0.093), the common carp “Majalaya” has chromosome variation size